Isolation of Catechin as Secondary Metabolites from Tea Leaves (Camellia sinensis var. Assamica) - INDRARIANI (NIM 10505022), DWITA
Camellia sinensis var. Assamica is the species of Indonesian tea product which is known of its large amount of catechins than any other tea from any other country. Catechins is the major constituent of tea leaves which is very well known of its antioxidants, anticarcinogenic, cariostatic, and cholesterolemic activity. The major type of catechins are (-)-epigallocatechin gallate (EGCG), (-)-epicatechin (EC), (-)-epicatechin gallate (EGC) and (-)-epigallocatechin (EGC). Beside those type of catechins, there are new type of catechins which is known as methylated catechins. This type of catechins are known of its antibacterial activity. The aim of this research is to isolate any kind of catechins and it’s derivatives using several methods. The extract of tea leaves is separated and purified using reversed phase column chromatography with polyamide as the adsorbent and normal phase column chromatography with silica gel as the adsorbent. Analysis and structure determination was done by High Performance Liquid Chromatography (HPLC), IR spectra, and 1H-NMR spectroscopic data. (-)-epicatechin was successfully isolated from tea leaves (Camellia sinensis var. Assamica) extract.